Estimating SMEs cost of equity using a value at risk approach : the capital at risk model - Beltrame, Federico; Cappelletto, Roberto; Toniolo, Gabriele; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
As well as reviewing traditional models, this book proposes an alternative model for estimating the cost of risk capital. This model, known as CaRM (Capital at Risk Model), bases the cost estimate of risk capital on VaR (Value at Risk) for the very first time. This book is an ideal resource for developing valuation research in SMEs.
Keywords: Finance; Business enterprises -- Finance; Corporations -- Finance; Banks and banking; Capital market